2015
DOI: 10.1242/jcs.164574
|View full text |Cite
|
Sign up to set email alerts
|

Rho kinase-dependent actin turnover and actomyosin disassembly are necessary for mouse spinal neural tube closure

Abstract: The cytoskeleton is widely considered essential for neurulation, yet the mouse spinal neural tube can close despite genetic and non-genetic disruption of the cytoskeleton. To investigate this apparent contradiction, we applied cytoskeletal inhibitors to mouse embryos in culture. Preventing actomyosin cross-linking, F-actin assembly or myosin II contractile activity did not disrupt spinal closure. In contrast, inhibiting Rho kinase (ROCK, for which there are two isoforms ROCK1 and ROCK2) or blocking F-actin dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(112 citation statements)
references
References 61 publications
12
100
0
Order By: Relevance
“…In support of this idea, we recently found that preventing actin turnover abrogates the progression of mouse PNP closure, whereas treatment with actomyosin inhibitors at concentrations compatible with continued development in culture does not significantly delay zippering (17,53). Indeed, because different cell types (neural vs. surface ectoderm) are involved in PNP narrowing and shortening, it seems reasonable that these cell types may be susceptible to different genetic or environmental impediments, leading to spina bifida through distinct mechanisms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In support of this idea, we recently found that preventing actin turnover abrogates the progression of mouse PNP closure, whereas treatment with actomyosin inhibitors at concentrations compatible with continued development in culture does not significantly delay zippering (17,53). Indeed, because different cell types (neural vs. surface ectoderm) are involved in PNP narrowing and shortening, it seems reasonable that these cell types may be susceptible to different genetic or environmental impediments, leading to spina bifida through distinct mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…This work has identified cellular behaviors, such as actomyosin-driven apical constriction of neural plate cells, required to initiate apposition of the neural folds (11)(12)(13)(14)(15)(16). Genetic or pharmacologic disruption of actin remodeling enzymes prevents NT closure in amphibians as well as in mice (16)(17)(18)(19). Moreover, progression of neurulation in mice Significance Neurulation has been intensively studied in lower vertebrates, but marked species differences call into question the relevance of these models for human neural tube (NT) closure.…”
mentioning
confidence: 99%
“…Pulsatile actin dynamics were recently observed in Xenopus neural tube closure (Christodoulou and Skourides, 2015), and disrupting pulses by elevating cytosolic Ca 2+ levels promoted neural tube defects. It was separately observed that the actin severing protein, cofilin, is important for neural tube closure (Escuin et al, 2015; Gurniak et al, 2005; Mahaffey et al, 2013). This suggests that actin turnover, and possibly actomyosin pulsing, is critical for neural tube morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from several studies in mice indicate that ROCK activity is crucial for fetal development, and that mouse spinal neurulation requires precise regulation of ROCK signaling. ROCK1 knockout mice display an embryonic lethal phenotype, and inactivation of ROCK1 in mice has led to morphological defects and failure of neural tube closure [45, 46]. …”
Section: Discussionmentioning
confidence: 99%